The Association of Visual Impairment With Clinical Outcomes in Hemodialysis Patients. Issue 19 (May 2016) - Hong, Yu Ah; Kim, Suk Young; Kim, Su-Hyun; Kim, Young Ok; Jin, Dong Chan; Song, Ho Chul; Choi, Euy Jin; Kim, Yong-Lim; Kim, Yon-Su; Kang, Shin-Wook; Kim, Nam-Ho; Yang, Chul Woo; et al.
Abstract : Abstract: Visual impairment limits people's ability to perform daily tasks and affects their quality of life. We evaluated the impact of visual impairment on clinical outcomes in hemodialysis (HD) patients. HD patients were selected from the Clinical Research Center registry a prospective cohort study on dialysis patients in Korea. Visual impairment was defined as difficulty in daily life due to decreased visual acuity or blindness. The primary outcome was all-cause mortality and the secondary outcomes were cardiovascular and infection-related hospitalization. A total of 3250 patients were included. Seven hundred thirty (22.5%) of the enrolled patients had visual impairment. The median follow-up period was 30 months. The Kaplan–Meier curve and log-rank test showed that all-cause mortality rates ( P < 0.001) as well as cardiovascular and infection-related hospitalization rates ( P < 0.001 and P < 0.001) were significantly higher in patients with visual impairment than in patients without visual impairment. In the multivariable analysis, visual impairment had significant predictive power for all-cause mortality (Hazard ratio [HR], 1.77, 95% confidence interval [CI], 1.21–2.61, P = 0.004) and cardiovascular hospitalization (HR 1.45 [1.00–1.90], P = 0.008) after adjusting for confounding variables. Of these 3250 patients, 634 patients from each group were matched by propensity scores. In the propensity score matched analysis, patients with visual impairment had independently significant associations with increased all-cause mortality (HR 1.69 [1.12–2.54], P = 0.01) and cardiovascular hospitalization (HR 1.48 [1.08–2.02], P = 0.01) compared with patients without visual impairment after adjustment for confounding variables. Our data demonstrated that visual impairment was an independent risk factor for clinical adverse outcomes in HD patients. Abstract : Supplemental Digital Content is available in the text